1999
DOI: 10.1002/(sici)1097-4644(19990201)72:2<286::aid-jcb13>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolactin on aldosterone secretion in rat zona glomerulosa cells

Abstract: Acute effects and action mechanisms of prolactin (PRL) on aldosterone secretion in zona glomerulosa (ZG) cells were investigated in ovariectomized rats. Administration of ovine PRL (oPRL) increased aldosterone secretion in a dose-dependent manner. Incubation of [3H]-pregnenolone combined with oPRL increased the production of [3H]-aldosterone and [3H]-deoxycorticosterone but decreased the accumulation of [3H]-corticosterone. Administration of oPRL produced a marked increase of adenosine 3',5'-cyclic monophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Previous studies have shown that PRL receptors (PRLR) are expressed in adrenal cortex in several species (McDonough and Ewig 1982;Klemcke et al 1989;Ouhtit et al 1993;Glasow et al 1996;Glasow et al 1998). In addition to its regulatory function in the reproductive system (such as in lactation), PRL has been shown to stimulate corticosterone secretion by primary rat adrenocortical cell cultures in-vitro (Lo et al 1998;Chang et al 1999;Kau et al 1999;Lo and Wang 2002;Kan et al 2003;Lo et al 2006;Jaroenporn et al 2007). These observations led us to postulate that stress-induced PRL elevation may enhance the secretion of corticosterone in response to stress.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that PRL receptors (PRLR) are expressed in adrenal cortex in several species (McDonough and Ewig 1982;Klemcke et al 1989;Ouhtit et al 1993;Glasow et al 1996;Glasow et al 1998). In addition to its regulatory function in the reproductive system (such as in lactation), PRL has been shown to stimulate corticosterone secretion by primary rat adrenocortical cell cultures in-vitro (Lo et al 1998;Chang et al 1999;Kau et al 1999;Lo and Wang 2002;Kan et al 2003;Lo et al 2006;Jaroenporn et al 2007). These observations led us to postulate that stress-induced PRL elevation may enhance the secretion of corticosterone in response to stress.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, prolactin administration has been associated with an increased aldosterone secretion by rat zona glomerulosa cells (35). These findings are suggestive of a possible influence on aldosterone release with a consequent salt-retaining effect, possibly resulting in a vasopressin-independent increase in water reabsorption.…”
Section: Discussionmentioning
confidence: 78%
“…Similar effects have been found for PRL o n s e c r e t i o n o f a l d o s t e r o n e , c o r t i s o l , d e h y d r o e p i a n d r o s t e r o n e ( D H E A ) a n d / o r dehydroepiandrosterone sulfate (DHEAS) in human and nonhuman primate adrenals [11, 19- 22]. Moreover, PRL increase in vitro secretion of corticosterone and aldosterone in rat adrenocortical cells [4,[23][24][25][26][27]. In the present study, PRL stimulation of adrenal steroid release was found to be dependent on Jak2 activity since PRL-induced adrenal steroid release was significantly prevented by AG490.…”
Section: Discussionmentioning
confidence: 99%